Striking the Balance: Navigating the Complexities of Intrauterine Infection and Inflammation (Triple I) for Better Maternal and Neonatal Outcomes - Athar, Sufia; Abedin, Sarfaraz (Disease and Health: Research Developments Vol. 5, 2025)
Intrauterine infection, inflammation or both (Triple I) is known to cause detrimental pregnancy outcomes. On one hand delay in the diagnosis of chorioamnionitis can potentially cause adverse pregnancy outcomes, on the other hand, over-diagnosis leads to inapt antibiotic use, prolonged neonatal intensive care unit (NICU) stay, disruption of mother-infant bonding, delays in breastfeeding, economic burden and emotional stress from the prolonged hospital and NICU stay. In the literature, many studies and reviews have discussed Triple I in detail. However, many issues with diagnosis and management remain unclear. This narrative review gives an insight into these issues and will aid not only in the diagnosis but also in the management of Triple-I.